Bangladesh farmers push for temporary flooding to correct Dutch polder failure. (13th January 2020) - Hanlon, Joseph
Abstract: Controlling floods and raising rice production in Bangladesh have been the centres of struggle for nearly a century—between North and South, and between engineering solutions and local knowledge. Decades of disastrous construction of dikes and polders led first to local protests, including cutting dikes, and then to a structured local solution known as tidal river management, which won the support of Bangladeshi scientists and academics. Suddenly, the global North has noticed and is rushing to catch up—asking what local farmers knew and their hydraulic engineers did not, while trying to maintain the dominance of aid industry engineers and technicians in Bangladesh.